Campus climate for diversity and its impact on sense of belonging - Marquez, Angela, author; Aragon, Antonette, advisor; Anderson, Myron, committee member; Anderson, Sharon, committee member; Chavez, Ernest, committee member; Kuk, Linda, committee member (Colorado State University. Libraries, 2017)
Intentional efforts toward recruitment and retention of diverse populations of students, faculty, and staff are essential for the evolution and development of higher education institutions. Progress relies on a commitment to diversity in all facets of the institution in order to embrace a population that continues to diversify. Through assessment and evaluation of current student populations, understanding the impact of this effort is realized through an evaluation of the environment. This study utilizes data previously gathered through a campus climate survey at one university. Guided by a Critical Race Quantitative Intersectionality (CRQI) Framework, a quantitative methodology and an intersectional data mining approach is performed. Analysis begins with demographic data disaggregated by race, and then separated by gender identity and first-generation status to investigate for differences between and within groups on an established Campus Climate for Diversity dimension and a Sense of Belonging dimension. The data are analyzed through ANOVAs, split-file ANOVAs, and Factorial ANOVAs. The results indicate statistical, significant differences between races on all measures of the Sense of Belonging dimension and differences within racial groups when analyzed at the intersection of gender identity. Last, through simple linear regression analysis, campus climate for diversity serves as a predictive variable to sense of belonging for students attending this university.
Keywords: critical race quantitative intersectionality; sense of belonging; diversity; campus climate for diversity